2023
DOI: 10.1177/17448069231182235
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of immune cells to cancer-related neuropathic pain: An updated review

Abstract: Given that the incidence of cancer is dramatically increasing nowadays, cancer-related neuropathic pain including tumor-related and therapy-related pain gradually attracts more attention from researchers, which basically behaves as a metabolic-neuro-immune disorder with worse clinical outcomes and prognosis. Among various mechanisms of neuropathic pain, the common underlying one is the activation of inflammatory responses around the injured or affected nerve(s). Innate and adaptive immune reactions following n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Recent advances in imaging and metabolic profiling have illuminated both the neuroanatomical networks within solid organs as well as their mechanistic impact on organ function [ 1 ]. Increasing evidence underlines the nervous system’s potent influence on the immune cells and tumor microenvironments within solid organs [ 2 ]. The nervous system regulates a broad spectrum of physiological and pathophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in imaging and metabolic profiling have illuminated both the neuroanatomical networks within solid organs as well as their mechanistic impact on organ function [ 1 ]. Increasing evidence underlines the nervous system’s potent influence on the immune cells and tumor microenvironments within solid organs [ 2 ]. The nervous system regulates a broad spectrum of physiological and pathophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Chronic pain caused by cancer, radiotherapy, or chemotherapy is associated with chronic neuroinflammation. Studies 14 , 15 have found that non-neural cells such as immune cells and cancer cells play an active role in the occurrence and development of pain. The severity of pain in patients with cancer is closely related to an adverse tumor microenvironment, and the increased nerve damage occurs in a more toxic tumor environment.…”
Section: Introductionmentioning
confidence: 99%